2017
DOI: 10.1016/j.eurpolymj.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of lignin-based chemical oleogels prepared using diisocyanate crosslinkers: Effect of the diisocyanate and curing kinetics

Abstract: In this work, alkali lignin together with different diisocyanates (hexamethylene diisocyanate (HDI), isophorone diisocyanate (IDI), toluene diisocyanate (TDI) and 4,4′methylenebis (phenyl isocyanate) (MDI)) have been tested as gelling agents in a castor oil medium. A two-step process comprising first lignin functionalization with a diisocyanate and then the formation of a bio-based polyurethane with gel-like characteristics by combining the functionalized lignin with castor was followed. FTIR and thermogravime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
(51 reference statements)
3
28
0
Order By: Relevance
“…This effect generated constraints for the benzoyl radical to attack the carbon double bond (C = C) of the acrylate chain during the propagation state of radical polymerisation. Meanwhile, JPUA-IPDI offered a more flexible, asymmetrical aliphatic structure of IPDI side chain with less steric hindrance [31]. This made JPUA-IPDI more favourable during the UV curing reaction compared to JPUA-TDI.…”
Section: Adhesion Testmentioning
confidence: 99%
“…This effect generated constraints for the benzoyl radical to attack the carbon double bond (C = C) of the acrylate chain during the propagation state of radical polymerisation. Meanwhile, JPUA-IPDI offered a more flexible, asymmetrical aliphatic structure of IPDI side chain with less steric hindrance [31]. This made JPUA-IPDI more favourable during the UV curing reaction compared to JPUA-TDI.…”
Section: Adhesion Testmentioning
confidence: 99%
“…The preparation of chemical oleogels was carried out following the procedure detailed by Borrero-López et al [16], wherein the NCOfunctionalized lignin samples, at 20% w/w concentration, were dispersed in castor oil at room temperature for 24 h, using a RW 20 IKA stirrer outfitted with an anchor impeller. Subsequently, the oleogels were stored at room temperature and characterized after one month, to ensure the complete curing of the samples [23]. Oleogel samples have been named as GAHL, GSEL, GEKL and GPKL for those prepared with lignins obtained from the autohydrolysis, steam explosion and eucalypt and pine kraft pulping treatments, respectively.…”
Section: Functionalization Of Residual Lignin Fractions and Oleogel Pmentioning
confidence: 99%
“…In this sense, Sánchez et al [8] and Núñez et al [9] evaluated the performance of cellulose derivatives-based oleogels and gel-like dispersions of industrial cellulose pulps, respectively. The potential use of chitin, chitosan and some acylated derivatives as biogenic thickening agents to formulate stable dispersions in vegetable oils was explored by Sánchez et al [10]; whereas Gallego et al [11] and Borrero-López et al [12] reported the preparation of oleogels using NCO-functionalized lignocellulosic materials for the same use.…”
Section: Introductionmentioning
confidence: 99%